Development of a new method to estimate the incident solar flux on central receivers from deteriorated heliostats. (January 2019) - Rodríguez-Sánchez, M.R.; Leray, C.; Toutant, A.; Ferriere, A.; Olalde, G.
Abstract: This work proposes a new empirical direct methodology to estimate both the solar flux distribution and intensity on the surface of central receivers. In solar power tower plants with deteriorated heliostats, the numerical simulations to estimate the incident solar flux are not precise. Hence the thermal behaviour of the receivers cannot be determined. In those cases, direct measurement or semi-empirical methodologies are required to characterize the radiant power on the receiver. The new methodology proposed, named "Superposition method", consists in the hourly characterization of the reflected solar beam of each individual heliostat by means of a pyrheliometer, a passive screen, a flux sensor, a camera and digital image analysis. According to the aiming strategy used during receiver operation, each individual solar flux distribution and intensity can be gathered to obtain the total incident radiant power on the solar receiver. This non-real-time method has the advantage of reproducing any solar flux distribution on the receiver at present and past time. Graphical abstract: Image Highlights: A semi-empirical methodology to estimate the incident solar flux on central receivers are proposed. This methodology has been named Superposition method. Superposition method is useful in deteriorated solar fields. Superposition method characterizes each heliostat individually. The error made in the flux estimation are comprised between 2.5 and 8%.